Pengaruh Manajemen Waktu Terhadap Produktivitas Akademik Mahasiswa S1 Prodi Administrasi Pendidikan Universitas Negeri Padang - Ismi, Dhiya Fadhillah; Novriyanti Achyar; Syahril; Enceria Damanik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is grounded in issues related to time management and its connection to students' academic productivity. This study aims to determine the effect of time management on the academic productivity of undergraduate students in the Educational Administration Study Program at Universitas Negeri Padang. This research employed a quantitative approach with a causal associative design. The population consisted of 606 undergraduate students, with a sample of 243 respondents selected through Simple Random Sampling. Data were collected using a Likert-scale questionnaire, which was tested on 30 respondents and found to be valid and reliable through SPSS analysis. Data analysis was conducted using simple linear regression, including t-test hypothesis testing and the coefficient of determination (R²). The results showed that students' academic productivity was in the very good category, with an achievement of 86.54%, while time management was in the good category, with a score of 75.42%. Time management contributed 68.7% to students' academic productivity, while the remaining 31.3% was influenced by other factors outside the scope of this study. These findings indicate that better time management is associated with higher academic productivity among students. Therefore, students are encouraged to improve their time management skills by setting clear learning goals, prioritizing academic tasks, creating regular schedules, avoiding procrastination, and developing a stronger sense of responsibility toward their academic obligations. Effective time management is expected to enhance students' academic productivity in a sustainable manner.